Development of a highly efficient single-mode microwave applicator with a resonant cavity and its application to continuous flow syntheses1. Issue 14 (19th February 2015) - Yokozawa, Saori; Ohneda, Noriyuki; Muramatsu, Ken; Okamoto, Tadashi; Odajima, Hiromichi; Ikawa, Takashi; Sugiyama, Jun-ichi; Fujita, Masashi; Sawairi, Taira; Egami, Hiromichi; Hamashima, Yoshitaka; Egi, Masahiro; et al.
<x xml:space="preserve">Abstract</x> A new microwave applicator specifically designed for continuous flow synthesis has been developed and tested in the Fischer indole synthesis and in the Diels–Alder reaction to afford the reaction products at a scale of 100 g h−1.